Fiscal consolidation and the probability distribution of deficits: A stochastic analysis of the stability pact - Andrew Hughes Hallett; Peter McAdam (University of Kent, Department of Economics, 2001)
Using stochastic simulations, this paper analyses the probability distribution of a country's deficit ratio under fixed exchange rates and a variety of monetary policy rules. The purpose is to show how the probability of getting an excessive deficit, defined as a deficit / GDP ratio in excess of 3% by Europe's Stability Pact, varies with different deficit target rules and different fiscal and monetary policy rules. We find that these fiscal ratios typically have a wide distribution, with fat tails and significantly longer tails on the upper side. That means fiscal targets may have to be country specific and conservative, and that fiscal policy has to be forward looking to keep the probability of excessive deficits below acceptable limits.
Keywords: E61; E63; 330; fiscal cushion; policy reaction functions; stochastic simulations; monetary union; Haushaltskonsolidierung; Haushaltsdefizit; Konvergenzkriterien; Europäische Wirtschafts- und Währungsunion; Theorie